La ejecución de la acción de protección en el derecho comparado: un análisis constitucional entre el Salvador y Ecuador - Bedoya Ugalde, Melany Vamary (2025)
This study presents a comparative law analysis of Ecuador's acción de protección (protection action) and El Salvador's recurso de amparo (writ of amparo), addressing key aspects such as normative evolution and historical context. The study highlights the protection action as an effective instrument for ensuring the recognition and restoration of constitutional rights, even emphasizing the necessity of enforcement actions to guarantee its execution. However, obstacles persist, such as inefficacy in providing timely restitution to the affected party due to the passive subject’s negligence in complying with judicial orders. In this context, El Salvador’s writ of amparo shares similarities, yet its execution has a broader scope, as evidenced by case law from its Constitutional Chamber. The study follows a qualitative methodology, given the theoretical nature of the collected information. The methods applied include deductive, descriptive, and analyticalcomparative approaches. For data collection, the study employed documentary review as a technique and comparative analysis as an instrument. The article concludes by recommending that Ecuador adopt more effective practices to ensure compliance with judicial decisions, taking into account the successful legal mechanisms implemented in El Salvador.